Projecting HIV prevalence among individuals aged 15-49 years in Bhutan using Holt’s double exponential smoothing model - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Bhutan from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will generally decline over the out of sample period. Therefore, policymakers must improve HIV case detection among key populations and implement relevant HIV preventive interventions recommended by the World Health Organization (WHO).
Keywords: Exponential smoothing; Forecasting; HIV prevalence